Good Governance In Community Empowerment In Bababulo Village, Majene Regency - Suadi, Nur Afifah; Nurlinah, Nurlinah; Syamsu, Suhardiman (Kemudi, 2024)
Abstract: This study aims to determine Good Governance in Community Empowerment of Bababulo Village, Majene Regency. This research was conducted using a descriptive qualitative approach. Data collection techniques used in this research include observation, interviews, and documentation. The data analysis techniques used are reduction, presentation, and conclusion drawing. The results of this study state that based on the results of research and field observations in the aspects of transparency, accountability, and responsiveness, it is concluded that good governance in empowering the Bababulo village community in Majene Regency shows maximum results. This is based on the three standard aspects that are indicators of good governance in community empowerment that can be fulfilled entirely. Although there are still some things that need to be addressed. But overall, the principles of good governance in empowering the Bababulo village community in Majene Regency can be said to be optimal. The limitation of this research is that it only focuses on analyzing the principles of good governance, the focal point of which is only three indicators of good governance principles, namely responsiveness, transparency, and accountability.